Fluid-Electrolyte Disturbances Related to Aneurysmal Subarachnoid Hemorrhage [Anevrizmatik Subaraknoid Kanama Cerrahisi Sonrasi Sivi-Elektrolit Bozukluklari] - (:unkn) unknown (My University, 2003)
In this retrospective study we aimed to demonstrate the incidence of cerebral originated-fluid and electrolyte disturbances and evaluate the diagnostic and treatment modalities in patients who underwent craniotomy for subarachnoid hemorrhage and aneursym clipping. We investigated the intensive care unit charts of patients ASA I-II, who underwent craniotomy for aneurysm clipping retrospectively. Serum sodium level and osmolality, urine density, total amount of fluid infused, urine output, central venous pressure, location of aneurysm and the days spent in the intensive care unit were evaluated. Patients were divided into 3 group; hyponatremic patients with serum sodium values <130 mEq L-1, serum osmolality <270mOsm kg-1 and urine density > 1010 mg dL-1 were called as Group cerebral salt wasting (Group S); hypernatremic patients with serum sodium values >145mEq L-1, serum osmolality >295 mOsm kg-1, urine density <1005 mg dL-1 and polyuri were called as Group diabetes insipidus (Group D) and normonatremic patients with serum sodium values 130-145, SOsm 270-295 mOsm kg-1 and urine specific gravity >1010 mg dL-1 were called as Group normal (Group N). The days spent in the intensive care unit were longer in Group S (9.4%) (22.33±14.04 days) than Groups D (34.4%) (8.0±4.2 days) and N (56.2%) (6.38±2.50 days) (p<0.01). Serum osmolality in Group S (263.0±5.0 mOsm kg -1) was lower than the other groups (p<0.001). According to the location of aneurysm, there were no difference at the incidences of Group S (22.2%) and D (22.2%) in aneurysm of middle cerebral arter. The incidence of Grup D (6.6%) was found higher than Group S (6.6%) in aneurysm of anterior communican artery. In conclusion, we decided that electrolyte imbalance was seen inpatient with subarachnoid hemorrhage frequently and might cause deterioration of underlying pathology results from vasospasm, cerebral edema, confusion, convulsion and coma. Therefore volume status and electrolyte imbalances must be taken into consideration in patients operated for SAH/aneurysm and its proper management must be performed.
Keywords: Aneurysm; Craniotomy; Elebctrolyte imbalance; Intensive care unit; Subarachnoid hemorrhage